Effect of Moringa Leaf Meal Supplementation on Haematological and Serum Biochemical Profile of Broiler Chicken - Lateef, Tijani; Adetayo, Akanji; Kudirat, Agbalaya; Murisiku, Onigemo (Indian Journal of Animal Nutrition, 2018)
The aim of this study was to evaluate the effects of feeding Moringa oleifera leaf meal (MOLM) on the haematological and serum biochemical profile of broiler chicken. A total of two hundred broiler unsexedchickens (Anak strain) were randomly allotted to five treatments. Each treatment onsisted of forty birds in five replicates. Shade dried MOLM was incorporated into the broiler starter and finisher diets at 0, 5, 10, 15 and 20% levels, respectively. The contents of tannin, phytic acid, saponin and oxalate were higher in the MOLM than fresh moringa leaves (FML). Dietary level of MOLM showed negative correlation with packed cell volume andhaemoglobin and values were reported lowest in 20% MOLM fed birds. However, white blood cell and neutrophil counts were found significantly (P